1987
DOI: 10.1007/bf00385042
|View full text |Cite
|
Sign up to set email alerts
|

Habitat structure and predators: choices and consequences for rodent habitat specialists and generalists

Abstract: Both habitat structure and risk of predation are thought to influence rodent community composition in different habitats, but experiments on the degree to which these factors determine the use of habitat by rodents are lacking. I sought to discover (1) if cover density altered habitat choice and (2) if cover density affected the vulnerability to predators of two rodents, a habitat specialist and a habitat generalist. In laboratory experiments, the habitat specialist, the red-backed vole (Clethrionomys gapperi)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 36 publications
1
19
0
2
Order By: Relevance
“…Also, the bullet-shaped bodies and short legs of prairie voles make them more susceptible to prédation (Wywialowski, 1987) because they are slow and clumsy. Hence, increasing predatory risk by reducing cover should lead to a greater decrease in vole density than in deer mouse or harvest mouse density, which was observed on grid K. Getz (1970) also concluded that a decline in numbers of M. pennsylvanicus following mowing and baling of vegetation could be attributed to heavy prédation, and Henttonen (1987) concluded that the social system of Microtus makes them especially susceptible to weasel prédation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the bullet-shaped bodies and short legs of prairie voles make them more susceptible to prédation (Wywialowski, 1987) because they are slow and clumsy. Hence, increasing predatory risk by reducing cover should lead to a greater decrease in vole density than in deer mouse or harvest mouse density, which was observed on grid K. Getz (1970) also concluded that a decline in numbers of M. pennsylvanicus following mowing and baling of vegetation could be attributed to heavy prédation, and Henttonen (1987) concluded that the social system of Microtus makes them especially susceptible to weasel prédation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, animals with large body size are more attractive to predators and suffer higher rates of predation than animals with smaller body size . Also, more agile animals are better at evading the attacks of predators (Bartholomew & Caswell, 1951;Wywialowski, 1987). In the case of rodents in Kansas grasslands, prairie voles (Microtus ochrogaster Bole Moulthrop, 1942) with relatively large body size and bullet-shaped body with short legs should be more vulnerable to predation than the other rodent species in the community; western harvest mice (Reithrodontomys megalotis Baird, 1858) with small body size and good climbing ability should be less vulnerable.…”
Section: Introductionmentioning
confidence: 99%
“…The predicted relationship between predatory risk and plant cover also is supported by experimental evidence. Thus, red-backed voles Clethrionomys gapperi and Egyptian sand gerbils Gerbillus pyramidum are less vulnerable to mammalian predators when in patches of greater density of cover than in patches of less cover (Wywialowski 1987, Kotler et al 1991, Longland and Price 1991. More interestingly, black-tailed prairie dogs avoid foraging at locations with short vegetation when group size is experimentally reduced (Kildaw 1995).…”
Section: The Predatory Risk Hypothesismentioning
confidence: 95%
“…Juveniles may be especially responsive to factors aff ecting predation risk, due to their high vulnerability to predation (Carey and Moore 1986). Although herbivores often use high visibility to detect predators at a distance (Blumstein et al 2006), they also use visual obstruction to seek refuge from predators (Wywialowski 1987, Sharpe and van Horne 1998, Hannon et al 2006.…”
Section: H C Wheeler and D S Hikmentioning
confidence: 99%